Three new species of Euphorbia subgenus Chamaesyce (Euphorbiaceae) endemic to Brazil - da Silva, Otávio Luis Marques; Braun, Pierre; Riina, Ricarda; Cordeiro, Inês (European Journal of Taxonomy, 2021)
We describe and illustrate three new species of Euphorbia subgenus Chamaesyce from Brazil: E. blepharadena O.L.M.Silva & Cordeiro sp. nov., E. longipedunculata O.L.M.Silva & Riina sp. nov. and E. sobolifera O.L.M.Silva & P.J.Braun sp. nov. Based on morphological characteristics, E. blepharadena sp. nov. and E. longipedunculata sp. nov. are placed in the subcosmopolitan section Anisophyllum, whereas E. sobolifera sp. nov. is placed in the more geographically restricted section Crossadenia. The three new species are compared with their most similar species in each section, and accompanied by comments on habitat and distribution, illustrations, photographs, and proposed conservation status.